Urgensi Penerapan Prinsip Checks and Balances dalam Pengaturan Kepala dan Wakil Kepala Otorita IKN - Rizky, Zulfikar Muhammad (UM Purwokerto Press, 2024)
This study explores the urgency of implementing the principle of checks and balances in the regulation of the Head and Deputy Head of the Nusantara Capital City Authority (IKN) according to Law Number 3 of 2022. The research addresses two main issues: (1) What are the roles and authorities of the Head and Deputy Head of the Nusantara Capital City Authority, and (2 What is the urgency of applying the principle of checks and balances to the Head and Deputy Head of the IKN Authority? Using a normative juridical approach, this study finds that the Head of the Authority holds the primary authority in directing and managing the development of IKN, while the Deputy Head plays a significant supporting role in performing administrative and operational functions. The study underscores the importance of checks and balances in preventing abuse of power and enhancing transparency and accountability in decision-making. To achieve an ideal checks and balances framework, the study recommends a clear division of authority, robust oversight mechanisms, regular evaluations, transparent decision-making processes, and the involvement of external oversight bodies. The effective implementation of the checks and balances principle is expected to maintain the integrity and accountability in the governance of the Nusantara Capital City Authority.